2014
DOI: 10.1523/jneurosci.1982-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

MiR-592 Regulates the Induction and Cell Death-Promoting Activity of p75NTRin Neuronal Ischemic Injury

Abstract: The neurotrophin receptor p75NTR has been implicated in mediating neuronal apoptosis after injury to the CNS. Despite its frequent induction in pathologic states, there is limited understanding of the mechanisms that regulate p75 NTR expression after injury. Here, we show that after focal cerebral ischemia in vivo or oxygen-glucose deprivation in organotypic hippocampal slices or neurons, p75 NTR is rapidly induced. A concomitant induction of proNGF, a ligand for p75 NTR , is also observed. Induction of this l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 44 publications
3
66
0
Order By: Relevance
“…For example, p75 NTR expression is induced in neurons after seizure (13,28), ischemia (15,29) and upon hypo-osmolar stress (14,30,31 (30,32), and both of which are activated by NGF (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, p75 NTR expression is induced in neurons after seizure (13,28), ischemia (15,29) and upon hypo-osmolar stress (14,30,31 (30,32), and both of which are activated by NGF (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional upregulation of p75 NTR expression has been shown to occur in neurons following brain acute injury (13)(14)(15) …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the expression change of miR‐592 in our study was highly consistent with that in focal cerebral ischaemia, which suggested that miR‐592 may also influence the apoptosis of retinal ganglion cells in eyes after an acute IOP elevation (Irmady et al. 2014). …”
Section: Discussionmentioning
confidence: 99%
“…NTR has been linked to neurodegeneration occurring in models of Alzheimer disease (20), amyotrophic lateral sclerosis (21), and ischemia (22)(23)(24)(25). Therefore, p75 NTR appears to function as a stress-activated receptor that promotes degeneration in response to neuronal injury.…”
mentioning
confidence: 99%